Comparative Analysis of Adjectives In English - Siagian, Elvi Riski Hidayati Br.; Damanik, Nazla Khairunnisa; Harahap, Hasti Ananda; Panjaitan, Zakiyah Darajah; Lubis, Yani (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This study aims to analyze the use of comparative adjectives in English by students at the State Islamic University of North Sumatra (UIN SU). Mastery of adjective comparison is important to improve English skills, both oral and written. The research uses a qualitative approach with an interview method to 20 students from various study programs. Interview questions include the use of adjectives in positive, comparative, superlative, as well as irregular adjectives and their exceptions. The results of the study revealed that students experienced difficulties related to the use of irregular adjectives, exceptions in the formation of comparisons, long adjectives, lack of practice and practice, and the influence of the mother tongue. These findings provide valuable information for the development of more effective teaching methods in the topic of adjective comparison in UIN SU. In addition, this research contributes to enriching English learning literature, especially in the context of Indonesian higher education.